A new species of Goeppertia (Marantaceae) from the atlantic forest of northeastern Brazil - Luna, Naédja; Pessoa, Edlley; Saka, Mariana N. [UNESP]; Alves, Marccus (Magnolia Press, 2016)
A new species from the Atlantic forest of northeastern Brazil, Goeppertia yoshida-arnsiae, is described and illustrated. It is morphologically similar to G. umbrosa (Körnicke 1862: 137) Borchsenius & Suárez (2012: 635), but differs mainly by the indumentum of the leaf blades and petioles, length of the peduncles, number of bracteoles per pair of flower, and indumentum of the sepals.
Keywords: Bahia; Marantaceae; Neotropics; Pernambuco